ETIOLOGICAL SPECTRUM AND CLINICAL PROFILE OF SYMPTOMATIC VAGINAL DISCHARGE AMONG WOMEN ATTENDING A TERTIARY CARE HOSPITAL: A PROSPECTIVE CROSS-SECTIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Symptomatic vaginal discharge is a frequent reproductive health complaint among women and may result from physiological changes or infections such as vulvovaginal candidiasis, bacterial vaginosis, trichomoniasis, and cervicitis. Considerable overlap among clinical manifestations often limits accurate etiological diagnosis based on symptoms alone. Objectives: To determine the etiological spectrum of symptomatic vaginal discharge among women attending a tertiary care hospital and to describe their demographic, clinical, and microbiological characteristics. Materials and Methods: A prospective cross-sectional study was conducted among 300 symptomatic women aged 15–55 years attending the outpatient departments of Dermatology, Venereology and Leprosy, Sexually Transmitted Diseases, and Obstetrics and Gynaecology at Government General Hospital, Suryapet, over a 12-month period during 2023–2024. Demographic, reproductive, contraceptive, and clinical histories were recorded. Vaginal specimens were subjected to pH estimation, saline wet mount, potassium hydroxide preparation, Whiff test, Gram staining, and culture. Sabouraud’s dextrose agar was used for fungal culture and CPLM medium for Trichomonas vaginalis. Endocervical specimens were examined microscopically and cultured where indicated. Results: Of the 300 participants, 184 (61.33%) were aged 15–25 years and 251 (83.6%) were married. Female sex workers constituted 90 (30%) participants. Foul-smelling discharge was the most common presenting complaint in 113 (37.6%) women, followed by itching/curdy discharge in 100 (33.4%) and excessive discharge in 87 (29%). A specific infectious etiology was identified in 101 (33.7%) women. Vulvovaginal candidiasis was the most frequent infection, occurring in 75 (25%), followed by bacterial vaginosis in 21 (7%), trichomoniasis in 3 (1%), and cervicitis in 2 (0.67%). The remaining 199 (66.3%) women were classified as having normal vaginal discharge/no specific infectious etiology. Conclusion: Vulvovaginal candidiasis was the predominant identifiable infectious cause of symptomatic vaginal discharge, followed by bacterial vaginosis. Considerable overlap among clinical presentations and the substantial proportion of women without a specific infectious diagnosis emphasize the importance of laboratory-supported etiological evaluation rather than symptom-based empirical management alone.